2015
DOI: 10.1111/evo.12581
|View full text |Cite
|
Sign up to set email alerts
|

Character displacement and the evolution of niche complementarity in a model biofilm community

Abstract: Colonization of vacant environments may catalyze adaptive diversification and be followed by competition within the nascent community. How these interactions ultimately stabilize and affect productivity are central problems in evolutionary ecology. Diversity can emerge by character displacement, in which selection favors phenotypes that exploit an alternative resource and reduce competition, or by facilitation, in which organisms change the environment and enable different genotypes or species to become establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 52 publications
4
52
0
Order By: Relevance
“…B. cenocepacia diversified into three distinct morphotypes, the two of which preferentially attached to the polystyrene surface, whereas the third mostly resided on the top of the biofilm (Ellis et al 2015). The productivity of this ecotype mix was elevated due to the so called niche complementarity effect (Poltak and Cooper 2011;Ellis et al 2015). Similar niche specialization was earlier observed in Pseudomonas fluorescens evolved in a static microcosm, where the population .…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…B. cenocepacia diversified into three distinct morphotypes, the two of which preferentially attached to the polystyrene surface, whereas the third mostly resided on the top of the biofilm (Ellis et al 2015). The productivity of this ecotype mix was elevated due to the so called niche complementarity effect (Poltak and Cooper 2011;Ellis et al 2015). Similar niche specialization was earlier observed in Pseudomonas fluorescens evolved in a static microcosm, where the population .…”
Section: Introductionsupporting
confidence: 55%
“…Evolutionary diversification tends to improve biofilm productivity as newly emerged variants specialize in occupying different niches thereby reducing competition (Rainey and Travisano 1998;Poltak and Cooper 2011;Ellis et al 2015;Flynn et al 2016). An excellent example derives from a comprehensive study of an opportunistic pathogen, Burkholderia cenocepacia, which was allowed to evolve in a form of submerged biofilm subsequently assembling on a polystyrene bead floating in the liquid medium (Poltak and Cooper 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By following the evolution of wrinkly colonies from a smooth B. cenocepacia ancestor, a phenomenon associated with biofilm infections, Dr. Cooper showed that selection favored mutations clustered in the wsp operon (43). Despite phenotypic differences among wrinkly mutants, they shared similar fitness properties in mixed biofilms and acted as early surface colonists, suggesting that strong selective forces drive the colonization of this common niche (44). Daniel López (Institute for Molecular Infectious Biology, Würzburg, Germany) described the evolution of antibiotic resistance in Staphylococcus biofilms using intraclonal competition.…”
Section: Evolution In Biofilms and The Impact Of The Environment On Bmentioning
confidence: 99%